The Use of a Mobile Learning Tool by Medical Students in Undergraduate Anatomy and its Effects on Assessment Outcomes. Issue 1 (19th April 2019) - Golenhofen, Nikola; Heindl, Felix; Grab‐Kroll, Claudia; Messerer, David A.C.; Böckers, Tobias M.; Böckers, Anja
Abstract : Hand‐held devices have revolutionized communication and education in the last decade. Consequently, mobile learning (m‐learning) has become popular among medical students. Nevertheless, there are relatively few studies assessing students' learning outcomes using m‐learning devices. This observational study presents an anatomy m‐learning tool ( eMed ‐App), an application developed to accompany an anatomy seminar and support medical students' self‐directed learning of the skeletal system. Questionnaire data describe where, how frequently, and why students used the app. Multiple choice examination results were analyzed to evaluate whether usage of the app had an effect on test scores. The eMed ‐App application was used by 77.5% of the students, mainly accessed by Android smartphones, and at students' homes (62.2%) in order to prepare themselves for seminar sessions (60.8%), or to review learning content (67%). Most commonly, students logged on for less than 15 minutes each time (67.8%). Frequent app users showed better test results on items covering eMed ‐App learning content. In addition, users also achieved better results on items that were not related to the content of the app and, thus, gained better overall test results and lower failure rates. The top quartile of test performers used the eMed ‐App more frequently compared to students in lower quartiles. This study demonstrated that many students, especially the high‐performing ones, made use of the eMed ‐App. However, the app itself did not result in better outcomes, suggesting that top students might have been more motivated to use the app than students who were generally weak in anatomy.